Methods and techniques of tooling in copper: virtues and practices in the metal craft production - Kamarudin, Zumahiran; Mash'al, Nawal (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
This paper aims to elaborate on how the virtues and practices can join in the enterprise of metal craft production as reflected in the studio project approach of Applied Arts and Design Studio. The rationale is that virtues of research into related area followed by design development, for and through proper craft practices is relatively novel and essential for successful outcome of studio project. Craft is traditionally associated with the making of objects that requires manual skill and experience while its production is to exercise skill based on knowledge. The paper sets out the context of craft in relation to the tooling in copper as a studio project activity for students of Applied Arts and Design majoring in Conservation. The craft of tooling in copper is bound to the understanding of method, sensibilities of materials and handling of techniques in the making process leading to the production of metal work with high technical and aesthetic values. It requires the need for creative research in the crafts prior to the studio and workshop practices giving a sense of experiential knowledge as the unifying of both activities. The outcome and contribution of the paper is a better understanding of the relationship between virtues and practices of craft production, which benefits the students to excel in the studio projects. The unifying of the good virtues and craft production is essential because of the potential and value of eliciting and transmitting of knowledge and skill for the development of craft production.